Seizure Outcomes in Patients With Surgically Treated Cerebral Arteriovenous Malformations. Issue 5 (November 2015) - von der Brelie, Christian; Simon, Matthias; Esche, Jonas; Schramm, Johannes; Boström, Azize
Abstract : BACKGROUND: Epilepsy is the second most common symptom in cerebral arteriovenous malformation (AVM) patients. The consecutive reduction of life quality is a clinically underrated problem because treatment usually focuses on the prevention of intracerebral hemorrhage. OBJECTIVE: To evaluate postoperative seizure outcome with the aim of more accurate counseling for postoperative seizure outcome. METHODS: From 1985 to 2012, 293 patients with an AVM were surgically treated by J.S. One hundred twenty-six patients with preoperative seizures or epilepsy could be identified; 103 of 126 had a follow-up of at least 12 months and were included in the analysis. The different epilepsy subtypes were categorized (sporadic seizures, chronic epilepsy, drug-resistant epilepsy [DRE]). Preoperative workup and surgical technique were evaluated. Seizure outcome was analyzed by using International League Against Epilepsy classification. RESULTS: Sporadic seizures were identified in 41% of patients (chronic epilepsy and DRE were identified in 36% and 23%, respectively). Detailed preoperative epileptological workup was done in 13%. Seizure freedom was achieved in 77% (79% at 5 years, 84% at 10 years). Outcome was significantly poorer in DRE cases. More extensive resection was performed in 11 cases with longstanding symptoms (>24 months) and resulted in better seizure outcome as well as the short duration of preoperative seizure history. CONCLUSION: Patients presenting with AVM-associated epilepsy have a favorable seizure outcome after surgical treatment. Long-standing epilepsy and the progress into DRE markedly deteriorate the chances to obtain seizure freedom and should be considered an early factor in establishing the indication for AVM removal. ABBREVIATIONS: AVM, arteriovenous malformation CE, chronic epilepsy DRE, drug-resistant epilepsy ILAE, International League Against Epilepsy SM, Spetzler-Martin scale SPS, sporadic seizures